Kudriasov Type Univalence Criteria for Some Integral Operators - Virgil Pescar; Nicoleta Breaz (Abstract and Applied Analysis)
We consider some integral operators defined by analytic functions in the open unit disk and derive new univalence criteria for these operators, using Kudriasov condition for a function to be univalent.